1994
DOI: 10.3354/cr004047
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracies in weather data and their effects on crop growth simulation results. I. Potential production

Abstract: In weather data sets used by crop modellers, lrregulanties occur as inaccuracies In data or as mlssing values In this investigation, the effect of such irregularlt~es in temperature and global radlation data on s~n~u l a t i o n results 1s studied for a s p n n g wheat crop growth simulat~on model From the Ilterature, the inaccuracy in tempelature and global iadlation data was estimated to b e 1 "C and 10%respectively Systematic over-or underestimation of the data using these values resulted in deviations in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Two crop scenarios, A and C, accounted for most of the error in predicting simulated maize yield (Table 3). Often the effects of errors in radiation in the performance of a crop model tend to cancel each out despite the non-linearity in the plants response to radiation (Nonhebel 1994). In this study, however, the sign of the simulated yield errors concurred with the respective of PET in 8 out of 9 cases (Table 3).…”
Section: Crop Simulation Resultsmentioning
confidence: 46%
“…Two crop scenarios, A and C, accounted for most of the error in predicting simulated maize yield (Table 3). Often the effects of errors in radiation in the performance of a crop model tend to cancel each out despite the non-linearity in the plants response to radiation (Nonhebel 1994). In this study, however, the sign of the simulated yield errors concurred with the respective of PET in 8 out of 9 cases (Table 3).…”
Section: Crop Simulation Resultsmentioning
confidence: 46%
“…Nonhebel (1994a) found that inaccuracies in solar radiation measurement of 10% and of daily temperature of 1°C in data used within a crop simulation model resulted in yield estimation errors of up to 1 t ha −1 . Maintaining meteorologically appropriate, synchronised relationships between individual weather variables is essential for models that represent entities with non-linear responses to driving variables such as biological systems (Nonhebel 1994b) and hydro-chemical processes (Soulsby 1995;Creed et al 1996). Thermal time accumulation, which depends not only on the mean daily temperature but the difference between daily maximum and minimum temperatures, is the key driver of plant and insect phenological development (Arnold and Monteith 1974;Jarvis et al 2003, respectively).…”
Section: Related Researchmentioning
confidence: 98%
“…Mearns et al (1996) found that 380 simulated wheat yields were sensitive to changes in both temperature and precipitation, which 381 depended on soil characteristics. Nonhebel (1994a) found that temperature and solar radiation data 382 errors generated up to 35% overestimation of yield. In water-limited conditions, the model was 383 sensitive to inaccuracies in precipitation and solar radiation data, but when there was sufficient 384 water, it was sensitive to errors in temperature and solar radiation data (1994b).…”
Section: Relative Importance Of Rainfall Temperature and Yield Datamentioning
confidence: 99%